Empowering Student Engagement: Video-Based Religious Practice in Indonesia: Memberdayakan Keterlibatan Siswa: Praktik Keagamaan Berbasis Video di Indonesia - Nisa, Mir’atun (Universitas Muhammadiyah Sidoarjo, 2024)
Various methods in religious education have their own challenges, especially the lecture method which is often considered monotonous, abstract, and supra-rational. In today's technological era, the one-way lecture method, where educators dominate and students only listen and take notes, is no longer recommended. One of the weaknesses of this method is the difficulty of lecturers to monitor students' understanding and the tendency of students to be passive and less motivated, so that learning becomes less effective. To overcome this problem, especially in learning Al-Islam and Kemuhammadiyahan (AIK II) which discusses Worship and Muamalah, the assignment method through a project to make a video of prayer practice can be an alternative that is more suitable for generation Z. This generation is known to be expressive, visual, and curious. This generation is known to be expressive, visual, likes instant information, and creative in utilizing technology. Video making allows them to combine elements of theory with their imagination and creativity, making learning more contextual and reflective. Unlike the conventional lecture method, this approach is expected to increase student engagement and motivation.